The Effect of Calcitonin Gene-Related Peptide (CGRP) on the Cytosolic Calcium Concentration and Force in Rat Intramural Coronary Arteries - M. Sheykhzade; N.C.B. Nyborg (The Scientific World Journal)
The aim of this study was to investigate the mechanism of CGRP-induced relaxation in intramural rat coronary arteries. By using FURA-2 technique, cytosolic Ca2+-concentration ([Ca2+]i) was measured during contraction of the vascular smooth muscle with receptor-dependent agonist (tromboxane A2 analogue U46619) and with high concentration of extracellular potassium. At a steady state of contraction, the increase in [Ca2+]i induced by 300 nM U46619 (100״x 14 nM, n = 7) was similar to that induced by 36 mM K+ (98 ״x 9 nM, n = 7). However, the active tension induced by 300 nM U46619 was significantly (p < 0.01) higher than that induced by 36 mM K+. CGRP concentration-dependently (10 pM - 10 nM) reduced both the [Ca2+]i and tension of coronary arteries precontracted with either U46619 or BAY K 8644, and also of resting coronary arteries in PSS. In 36 mM K+-depolarized arteries, CGRP reduced only the tension without affecting the [Ca2+]i. In 300 nM U46619 precontracted arteries, pretreatment with 10 μM thapsigargin significantly (p < 0.05) attenuated the CGRP-induced reduction in the tension (but not [Ca2+]i). In 300 nM U46619 precontracted arteries, pretreatment with either 100 nM charybdotoxin or 100 nM iberiotoxin or 10 nM felodipine significantly (p < 0.05) attenuated the CGRP-induced reduction in both [Ca2+]i and the tension. In contrast, 1 μM glibenclamide did not affect the CGRP-induced responses in these coronary arteries. In resting coronary arteries, only pretreatment with the combination of 1 μM glibenclamide and 100 nM charybdotoxin attenuated the CGRP-induced decrease in the [Ca2+]i and tension, suggesting a different mechanism of action for CGRP in resting coronary arteries. We conclude that CGRP relaxes precontracted rat coronary arteries via three mechanisms: (1) a decrease in [Ca2+]i by inhibiting the Ca2+ influx through membrane hyperpolarization mediated partly by activation of BKCa channels, (2) a decrease in [Ca2+]i presumably by sequestrating cytosolic Ca2+ into thapsigargin-sensitive Ca2+ storage sites, and (3) a decrease in the Ca2+ -sensitivity of the contractile apparatus.